INVESTIGATION OF CLAY SWELLING PROBLEM DURING THERMAL OIL RECOVERY IN EAST MOLDABEK OIL FIELD, KAZAKHSTAN - Yesmukhambet, Madi (Nazarbayev University School of Mining and Geosciences, 2024)
In sandstone oil fields like those in Kazakhstan, steamflooding is a vital technique for enhancing oil recovery. However, a significant challenge arises from the swelling of clay minerals in reservoirs, causing permeability damage and impeding oil production. This thesis investigates clay swelling phenomena in sandstone oil reservoir in Kazakhstan, where smectite-illite clays constitute 40% of the reservoir rock. The scope of work encompasses a comprehensive examination of clay swelling behavior and its impact on permeability degradation by conduction a set of static and dynamic tests. Key objectives include study of temperature and salinity effect on clay swelling index and permeability reduction during dynamic coreflooding tests, determination of critical swelling concentrations and flow rates under different temperature and salinity regimes. The obtained results showed that at low salinity and high temperature conditions the clay swelling increases leading to serious permeability impairment. The results showed that at high salinities (4920-2000 mg/L) the swelling rate is low while at salinity range from 2000-0 mg/L is relatively higher. During static swelling test the highest expansion of clays of 2.25 times increase in volume was experienced at 200℃ and DW saturation. The CSC increases with temperature leading to higher swelling degree of clays. Increasing temperature and decreasing salinity leads to high permeability impairment. It was found that at critical swelling concertation (CSC) of 2.5NK no clay swelling was observed and permeability did not change at any temperature with an average value of 6.7mD. Generally, the critical flow rate drops by 0.1 cc/min when salinity lowers. The maximum permeability drop by 73.3% was observed at 150℃ and DW flooding. The comparison between static and dynamic results revealed that clay swelling degree is consistent between static and dynamic tests. The findings of this study will enhance our understanding of clay swelling under conditions resembling those of steamflooding, encompassing changes in salinity and temperature. Moreover, these results could inform the development of potential solutions to address and alleviate clay swelling issues in Kazakhstan's oil field.
Keywords: clay swelling; thermal oil recovery; East Moldabek Oil Field; Type of access: Embargo